Gender, Sport and the Media - Daddario, Gina (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
COURSE OBJECTIVE: Gender, Sport and the Media is a multidisciplinary special topics course that brings together the areas of sport sociology, gender studies, and media criticism, and fulfills elective requirements in kinesiology, mass communication and women’s studies. This course considers how the media depict images of gender and sport through an examination of media texts, including sports broadcasts, newspaper and magazine articles, and documentary and feature film. We will also consider the socio-cultural issues that have shaped sport, such as the impact of Title IX legislation, the commercialization of sport, the commodification of male and female athletes, the reproduction of masculinity and sport, among others. The goal of the course is to increase students’ awareness of the mass media’s role in shaping perceptions of gender and sport. Students will be encouraged to consider the relationship between media coverage of female athletes and the status of women in Western society